Diversity index of the insect population in cowpea and corn intercropping - Quinderé, Mary Ann Weyne; Santos, José Higino Ribeiro dos (Pesquisa Agropecuaria Brasileira, 2014)
This research was carried out at the Fazenda Experimental Vale do Curu at Pentecoste, CE, Brazil. The total diversity index and those of the parasites and predators of the cowpea ( Vigna unguiculata (L.) Walp) and corn, (Zea mays L.) cultivated in both intercropping and single crop system. The lowest total diversity index occurred with cowpea as single crop (0,24) and the highest with the treatments corresponding to cowpea planted after corn (0,33). As for the parasites and predators, the corn as single crop showed the highest diversity index, while the plots planted with corn and cowpea together presented the lowest index. The results allowed to conclude that the Hymenoptera Chelonus sp is an efficient natural enemy of the Spodoptera frugiperda. On the other hand, the parasites Diptera of the Tachinidae and Sarcophagidae families are more abundant in single corn than in the cowpea x corn intercropping systems and in the cowpea as a single crop.